2020
DOI: 10.1017/s1049023x20000916
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Non-Invasive Blood Pressure Measurement Strategies with Intra-Arterial Measurement

Abstract: Introduction: It is difficult to obtain an accurate blood pressure (BP) measurement, especially in the prehospital environment. It is not known fully how various BP measurement techniques differ from one another. Study Objective: The study hypothesized that there are differences in the accuracy of various non-invasive blood pressure (NIBP) measurement strategies as compared to the gold standard of intra-arterial (IA) measurement. Methods: The study enrolled adult intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Recently, it was reported that non-invasive cuff BP failed to identify 28% of isolated systolic hypertension cases, suggesting the need to improve cuff BP measurements ( 14 ). In ICUs, it was also shown that non-invasive BP measurement significantly underestimated BP compared with IBP measurement ( 15 ). Moreover, differences between non-invasive and IBP measurements have been shown to trigger low-risk treatment decisions in 20% of the patients in the ICU ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that non-invasive cuff BP failed to identify 28% of isolated systolic hypertension cases, suggesting the need to improve cuff BP measurements ( 14 ). In ICUs, it was also shown that non-invasive BP measurement significantly underestimated BP compared with IBP measurement ( 15 ). Moreover, differences between non-invasive and IBP measurements have been shown to trigger low-risk treatment decisions in 20% of the patients in the ICU ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 It is essential to acknowledge that noninvasive methods can measure only SBP but not DBP reliably. 10 The pathophysiology of an abnormal BP response is still not fully clear. 1 BP is regulated by peripheral vascular resistance and cardiac output (CO, defined as heart rate (HR) × stroke volume).…”
Section: Pathophysiology Of Hre In Different Populationsmentioning
confidence: 99%
“…2,3 However, in critically ill patients, non-invasive BP measurement is prone to underestimation of systolic BP. 4 What are the contraindications and complications?…”
Section: What Are the Indications?mentioning
confidence: 99%
“…While both non‐invasive and arterial BP measurement can be prone to artefact and error, there appears to be generally good correlation between mean arterial pressure measured via non‐invasive methods and invasive arterial methods 2,3 . However, in critically ill patients, non‐invasive BP measurement is prone to underestimation of systolic BP 4 …”
Section: What Are the Indications?mentioning
confidence: 99%